1992
DOI: 10.1164/ajrccm/146.4.1084
|View full text |Cite
|
Sign up to set email alerts
|

Chest Radiography and High Resolution Computed Tomography of the Lungs in Asthma

Abstract: CT scans have been studied only in asthmatics who were smokers, and no such study has been performed in patients with chronic uncomplicated asthma where a permanent bronchial destruction is likely to occur after a long course of the disease. The object of the study was to characterize CT-scan abnormalities and determine whether bronchial destructive lesions may be observed. Fifty-seven adults with chronic asthma of variable severity and etiology and 10 normal subjects were studied. None of the subjects smoked.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
102
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 2 publications
9
102
1
1
Order By: Relevance
“…The patient's chest CT was very helpful in the differential diagnosis of the cause of acute respiratory failure. The presence of lobar collapse and mucoid impaction have been previously described as reversible findings in the CT of asthma patients (5). Furthermore, necropsy descriptions of fatal asthma cases report lung overinflation associated with areas of atelectasis and bronchial and bronchiolar occlusion by mucus plugs (6), both of which were also found in this patient's CT.…”
Section: Discussionsupporting
confidence: 52%
“…The patient's chest CT was very helpful in the differential diagnosis of the cause of acute respiratory failure. The presence of lobar collapse and mucoid impaction have been previously described as reversible findings in the CT of asthma patients (5). Furthermore, necropsy descriptions of fatal asthma cases report lung overinflation associated with areas of atelectasis and bronchial and bronchiolar occlusion by mucus plugs (6), both of which were also found in this patient's CT.…”
Section: Discussionsupporting
confidence: 52%
“…CT scans of asthmatic patients have shown both decreased and increased bronchial lumen area, excessive airway narrowing in response to a variety of stimuli and airway wall thickening, in addition to mosaic perfusion and gas trapping on expiration [63][64][65][66][67][68]. LYNCH et al [65] found that 77% of asthmatic patients and 153 (36%) of 429 bronchi assessed in asthmatic patients had an internal bronchial diameter to pulmonary artery diameter ratio .1.…”
Section: Airway Imaging In Asthma Airway Dimensionsmentioning
confidence: 99%
“…5 Hence, it has been recommended that asthma be optimally controlled before HRCT assessment to exclude the influence of the potentially reversible airway changes that can occur in a radiological study of airway structural changes. 2,21 In our study, a population composed of subjects with mild intermittent asthma that was under control underwent HCRT, performed by the same experienced radiologist, to measure both the segmental and subsegmental airways. Our findings revealed that subjects and control subjects were similar in terms of total and subsegmental bronchial wall thickness, while significantly higher bronchial wall area was determined in terms of total segmental and subsegmental regions, consistent with the predominant involvement of peripheral small airways in subjects than in control subjects.…”
Section: Discussionmentioning
confidence: 99%